Implementación de Metadatos Dublín Core y protocolos de interoperabilidad para la plataforma científica EcuCiencia de la Universidad Técnica de Cotopaxi. - Robles Campoverde, Alba Cristina (2020)
This research was carried out in the scientific platform Equciencia of the Technical University of Cotopaxi, the main objective of this proposal is the implementation of Dublin Core metadata and interoperability protocols for the search of scientific articles, books and papers, in addition, it should be noted that research methods and techniques were carried out such as: bibliographic sources, interviews and observations, which helped to understand the needs of the development of the application. It was necessary to use open source tools such as Python, Django framework, PostgreSQL database, descriptive metadata and the OAI-PMH protocol. This protocol is a metadata harvester that allows us to obtain any type of information and for its management the iterative and incremental methodology was applied, it was developed through two iterations and each one lasted 45 days, also in each iteration was used the stage of analysis, design, implementation and tests were used. The final result of the project is the union of all the iterations achieving the successful implementation of the metadata elements Dublin Core Title, Creator, Description, Date, Subject, Publisher and Type in the scientific articles, books and papers of the platform, so it is concluded that the time of file search that the scientific platform Ecuciencia has was optimized, benefiting teachers of the Technical University of Cotopaxi, students and external users to perform their research from any search engine.